Diversity Perceptions in the UK Retail Industry: A Case of Tesco - Walid Ahmed; Asim Majeed; Ayesha Asim (International Journal of Management and Data Analytics)
It can be argued that with exponential technological changes like the emergence of artificial intelligence, machine learning, the internet of things (IoT), etc. retailers around the world are facing continuous challenges in keeping their business model updated and relevant for sustainable business growth and profitability. This study investigates whether diversity in the workforce plays a significant role in sustaining an organization. A survey was conducted to gauge the perceptions of employees in one of the UK’s leading retailers - Tesco, and what they thought of a heterogenous workforce on its impact on creativity, innovation, team cohesiveness, and branding of an organization’s image. While the majority agree that diversity in the workforce significantly improves the work culture and customer service, a reasonable minority feel otherwise. The findings of this research can be beneficial to students trying to understand the impact of Inclusion, Diversity, and Equity on organizations, employees in the retail industries, government, and other private industry stakeholders.